Charge transfer in crystalline germanium/monolayer MoS2 heterostructures prepared by chemical vapor deposition. Issue 44 (6th October 2016) - Lin, Yung-Chen; Bilgin, Ismail; Ahmed, Towfiq; Chen, Renjie; Pete, Doug; Kar, Swastik; Zhu, Jian-Xin; Gupta, Gautam; Mohite, Aditya; Yoo, Jinkyoung
Abstract : Heterostructuring provides novel opportunities for exploring emergent phenomena and applications by developing designed properties beyond those of homogeneous materials. Abstract : Heterostructuring provides novel opportunities for exploring emergent phenomena and applications by developing designed properties beyond those of homogeneous materials. Advances in nanoscience enable the preparation of heterostructures formed incommensurate materials. Two-dimensional (2D) materials, such as graphene and transition metal dichalcogenides, are of particular interest due to their distinct physical characteristics. Recently, 2D/2D heterostructures have opened up new research areas. However, other heterostructures such as 2D/three-dimensional (3D) materials have not been thoroughly studied yet although the growth of 3D materials on 2D materials creating 2D/3D heterostructures with exceptional carrier transport properties has been reported. Here we report a novel heterostructure composed of Ge and monolayer MoS2, prepared by chemical vapor deposition. A single crystalline Ge (110) thin film was grown on monolayer MoS2 . The electrical characteristics of Ge and MoS2 in the Ge/MoS2 heterostructure were remarkably different from those of isolated Ge and MoS2 . The field-effect conductivity type of the monolayer MoS2 is converted from n-type to p-type by growth of the Ge thin film on top of it. Undoped Ge on MoS2 is highly conducting. The observations can be explained by charge transfer in the heterostructure as opposed to chemical doping via the incorporation of impurities, based on our first-principles calculations.